Position and Role of Witnesses in Making Notarial Deeds Based on the Notarial Law on the Cancellation of Authentic Deeds to Become Private Deeds (Case Study of Supreme Court Decision Number 1266 K/PDT/2022) - Sudiro, Amad; Lestari, Mega Wahyu (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
An authentic deed is written evidence which has perfect legal force in the civil law system in Indonesia. This deed is made by or before an authorized public official, namely a notary, in accordance with the form and procedures determined in the laws and regulations. However, in practice, deeds are often found that do not meet formal and material requirements so that it causes legal problems and harming the parties involved. One of these problems can be seen in the Supreme Court's Cassation Decision Number 1266 K/Pdt/2022, where the notarial deed was made without being attended and signed by witnesses, which is a violation of the provisions of Article 38 paragraph (4) letter c and Article 40 paragraph (1) of Law No. 30 of 2004 concerning the Position of Notary, and Article 1868 of the Civil Code. This study used a normative legal method with a statute approach and a case approach. The data collection technique was conducted through literature studies and analyzed descriptively qualitatively. The results of the study show that notarial deeds which do not meet formal legal requirements, such as not being attended by witnesses, result in the legal status changing to a private deed. In this case, a notary as a public official can be held legally accountable, either administratively, civilly, criminally, or through a professional code of ethics. Thus, the fulfillment of formal and material requirements in the making of a deed by a notary is an important aspect in ensuring legal certainty and protection for the parties.